Detection of the new HLA‐DRB1*14:129 allele in a voluntary stem cell donor. Issue 4 (20th March 2013) - Testi, M.; Battarra, M.; Stellitano, C.; Condello, R.; Andreani, M.
Abstract : The new allele, officially named HLA DRB1*14:129, differs from HLA DRB1*14:54 in exon 2.